Microbiological quality of water used for human consumption in the extreme western region of Santa Catarina, Brazil - Scapin, Diane (2012)
This study aimed at evaluating the microbiological quality of water consumed by the population in the far western region of the state of Santa Catarina, Brazil. This region is primarily agricultural with cattle and swine production activities, factors that can influence on the microbiological water quality, mainly because usually these sources are not adequately protected and the waste are incorrectly discarded. Two hundred and ninety-eight water samples collected from several area in this region were evaluated from 2007 to 2010. Microbiological analyzes (total and fecal coliforms) were performed by means of multiple tube fermentation technique, as prescribed by the APHA (1998), according to Instruction 62, August 26, 2003 – Brazilian Ministry of Agriculture, Livestock and Supply. Of 298 samples, 191 (64.1%) were inappropriate for human consumption, according to the bacteriological standards established by Decree 518/2004 of the Brazilian Ministry of Health. Of the analyzed samples, 191 (64.1%) showed total coliforms, and the total and themotolerant coliforms were detected in 168 (56.4%) samples. These results are worrisome, and indicate that the preventive measures and adequate water treatment need to be implemented for preventing the occurrence of waterborne diseases.